The science of biological decomposition effective composting methods - Harrigan, Jim; Clokey, Joe; San Luis Video Publishing (Los Osos, California : San Luis Video Publishing, 1993)
This program starts on the microscopic level to see the wide array of micro and macro organism which work to break down organic matter. See how to create compost and explore its water and nutrient holding capacity
Title from title screen
Advisor, Mark Skinner
DVD format
Keywords: Compost; Organic fertilizers; Organis wastes